👤

Sinh(x+y)=sinhx coshy+coshx sinhy

Răspuns :

Răspuns:

demonstrație

Explicație pas cu pas:

[tex] \sinh(x + y) = \frac{{e}^{x + y} - {e}^{- x - y} }{2} \\ = \frac{ 2{e}^{x + y} - 2{e}^{ - x - y} }{4} \\ =\frac{ 2{e}^{x + y} + ( {e}^{x-y} - {e}^{y - x}) - ( {e}^{x-y} - {e}^{y - x}) - 2{e}^{ - x - y} }{4} \\ = (\frac{ {e}^{x + y} + {e}^{x-y} - {e}^{y - x} - {e}^{ - x - y} }{4}) + (\frac{ {e}^{x + y} - {e}^{x-y} + {e}^{y - x} - {e}^{ - x - y} }{4}) \\ = ( \frac{e ^{x} - {e}^{ - x} }{2} )(\frac{e ^{y} + {e}^{ - y} }{2}) + ( \frac{e ^{x} + {e}^{ - x} }{2} )(\frac{e ^{y} - {e}^{ - y} }{2}) \\ = \sinh(x) \cosh(y) + \cosh(x) \sinh(y) [/tex]